First detection of vanB phenotype-vanA genotype vancomycin-resistant enterococci in Egypt - Rasha MM Khairy; Mahmoud Shokry Mahmoud; Mona Abdel Monem Esmail; Aya Nabil Gamil (Journal of Infection in Developing Countries)
Introduction: Enterococci have emerged in last two decades as serious hospital acquired pathogens particularly vancomycin resistant strains (VRE). The study aimed to identify the prevalence of enterococcal isolation from hospital infections and colonization as well as determine vancomycin resistance phenotypes and genotypes. Methods: Sixty enterococcus isolates were isolated from patients, health care workers and hospital environment, identified and tested for antimicrobial susceptibility. Enterococcus species were identified by Real-time PCR and vancomycin resistance was assessed by agar dilution method and Real-time PCR.